Integrating Metabolomics and Network Analysis for Exploring the Mechanism Underlying the Antidepressant Activity of Paeoniflorin in Rats With CUMS-Induced Depression - Lei, Chaofang; Chen, Zhigang; Fan, Lili; Xue, Zhe; Chen, Jianbei; Wang, Xihong; Huang, Zhen; Men, Yinian; Yu, Mingzhi; Liu, Yueyun; Chen, Jiaxu (Frontiers in Pharmacology, 2022)
Background: Paeoniflorin (PF) represents the major bioactive constituent of the traditional Chinese medicine plant Paeonia suffruticosa (Ranunculaceae), which has a long history as a folk medicine in Asian. Paeoniflorin, a bitter pinene monoterpene glycoside, has antidepressant effects, but its potential therapeutic mechanism has not been thoroughly explored. Methods: Experimental depression in rats was established by the chronic unpredictable mild stress (CUMS) combined with orphan method, and the efficacy of paeoniflorin on depression was evaluated by the sucrose preference test and open field test. The antidepressant mechanism of paeoniflorin was investigated by metabolomic and network pharmacology. The relevant pathways of biomarkers highlighted in metabolomics were explored, and the possible targets of paeoniflorin in the treatment of depression were further revealed through network analysis. The binding activity of paeoniflorin to key targets was verified by molecular docking. Results: Metabolomics showed that rats with CUMS-induced depression had urine metabolic disorders, which were reversed by paeoniflorin through the regulation of metabolic pathways. Metabolites that play a key role in the function of paeoniflorin include citric acid, thiamine monophosphate, gluconolactone, 5-hydroxyindoleacetic acid and stachyose. Key predicted targets are SLC6A4, TNF, IL6 and SLC6A3. An important metabolic pathway is the Citrate cycle (TCA cycle). Conclusion: Network integrative analysis in this study showed that paeoniflorin could improve depressive-like symptoms in model rats with CUMS-induced depression and overall correct the disordered metabolic profile through multiple metabolic pathways.